Histopathological features of endometrium in those with symptoms suggestive of female genital tuberculosis - Sankareswari, R.; Sundharam, Ramya Sreevarshni Shunmugha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Histological characteristics of endometrial biopsy material as assessed by light microscopy remain the diagnostic standard for the clinical diagnosis of endometrial pathology. Management of female genital TB is not complete without tissue diagnosis. The aim of the present study was to find out the histopathological pattern of the endometrium in those with symptoms suggestive of genital tuberculosis. Methods: A random sample of 200 female OPD patients with symptoms suggestive of FGTB attending to the Obstetrics and Gynaecology OPD in a tertiary care hospital at Ariyur, Puducherry were subjected to endometrial curettage and histological characteristics of endometrial biopsy material was assessed. Results: Endometrial histopathology revealed proliferative endometrium (60.5%, n=121), secretary endometrium (25.5%, n=51) and menstrual endometrium (9%, n=18) in majority. Chronic endometritis (3%, n=6), Simple hyperplasia without atypia (1%, n=2), atrophic (0.5%, n=1) and inert endometrium (0.5%, n=1) were other abnormalities reported. Conclusions: Histopathological features of endometrium in those with suggestive symptoms of female genital TB are variable and non-specific.